Online Assessment in the Spotlight: A Case Study in a Spanish University - Marín, Victoria (2024)
Objective. This exploratory case study aims to analyze the attitudes, practices and preferences of higher education faculty and students in relation to online assessment. Methodology. A quantitative methodology based on a questionnaire was used, and a descriptive and correlational analysis was conducted. Participants included students and faculty members from a Spanish on-site university. Results. Certain similarities and differences in attitudes, practices and preferences between students and teachers are presented. Some relationships, albeit weak, were also identified between the online assessment practices used and some characteristics of the teachers’ profile or teaching (teaching experience, teaching load and class size). Conclusions. The findings show that a large part of the teaching staff shows some reluctance in the design and implementation of online assessment strategies beyond traditional exams, as well as a great concern about student control and the danger of fraud. On the other hand, students show generally more positive attitudes towards online assessment than the teaching staff. The recommendations point to the consideration of the role of institutional support and teacher training units for the improvement of teachers’ digital competence in relation to online assessment, the importance of updating security systems in technical infrastructures, and adjusting the effects of teaching load and class size when online assessment is applied.